Highly Specialized Optical Metrology - Pustelny, Tadeusz (Photonics Letters of Poland, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->This editorial contains the overview of the contents of the current issue of the Photonics Letters of Poland, devoted mainly to the optical metrology. A series of 14 papers deals both with technology, as well as pure and applied physics.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->